2022
DOI: 10.3390/pharmaceutics14051110
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Gold Nanorods@DNA Self-Assembled Drug-Loading System for Cancer Thermo-Chemotherapy in the Second Near-Infrared Optical Window

Abstract: In terms of synergistic cancer therapy, biological nanomaterials with a second near-infrared (NIR-II) window response can greatly increase photothermal effects and photoacoustic imaging performance. Herein, we report a novel stimuli-responsive multifunctional drug-loading system which was constructed by integrating miniature gold nanorods (GNR) as the NIR-II photothermal nanorods and cyclic ternary aptamer (CTA) composition as a carrier for chemotherapy drugs. In this system, doxorubicin hydrochloride (DOX, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Infrared thermal imaging has also been used to analyze skin tissues and identify tissues whose imaging is uneven to diagnose gynoid lipodystrophy [ 68 ]. This technology has also promoted the development of drug carrier materials with thermal imaging properties [ 69 ]. With this updated technology, digital infrared thermography, dynamic infrared thermography, and other derivative technologies were emerged during the development of infrared thermal imaging [ 66 , 70 ].…”
Section: Infrared Thermal Imaging Technologymentioning
confidence: 99%
“…Infrared thermal imaging has also been used to analyze skin tissues and identify tissues whose imaging is uneven to diagnose gynoid lipodystrophy [ 68 ]. This technology has also promoted the development of drug carrier materials with thermal imaging properties [ 69 ]. With this updated technology, digital infrared thermography, dynamic infrared thermography, and other derivative technologies were emerged during the development of infrared thermal imaging [ 66 , 70 ].…”
Section: Infrared Thermal Imaging Technologymentioning
confidence: 99%
“…In the 27 included articles, we found that studies that presented thermal or photocatalytic effects by using NIR on AuNPs. Most AuNP therapeutic applications are based on their ability to generate tunable heat upon exposure to NIR radiation, which is helpful in both NIR-responsive cargo delivery and photothermal/photodynamic therapies [70,71]. AuNPs exhibited remarkable absorption in the NIR region.…”
Section: Influence Of Nir On Antibacterial Effects Of Aunpsmentioning
confidence: 99%